Kebijakan Pengelolaan Aset dan Barang Milik Daerah di Pemerintah Provinsi Bali - I Gede Agus Wibawa; Dewa Ketut Suryawan (Public Inspiration : Jurnal Administrasi Publik, 2025)
In fact, the issue of regional assets and property is a serious problem that must be handled well by all regional governments. The release or publication of one of the BPK RI auditors entitled "Unraveling the Tangled Thread of Regional Government Fixed Assets" shows that there are many problems with regional assets and property. which has not been arranged properly and correctly. The phenomenon of still chaotic management of regional government assets encourages researchers to want to study/analyze management policies (governance) of regional assets and goods, in this case within the scope of the Bali Provincial Government. The above wishes become even more interesting to examine in more depth considering that some time ago the Bali Provincial Government exchanged land for the Bali Provincial Archives and Library Service, Bali Provincial Cooperative Service Land with former land. Galian C Tukad Unda Klungkung with the Bali Province High Prosecutor's Office. Proper management of assets and Regional Property (BMD) will be able to provide additional Regional Original Income (PAD), either through a rental system or a cooperative system for asset utilization.